Computer simulation of a series excited synchronous motor - Özdemir, M; Öngilbin, G (Taylor & Francis Inc, 2003)
This study attempts to build up a mathematical model for a type of series excited synchronous motor. This model, when used for simulation, is expected to yield the dynamic behavior of the system for typical cases such as asynchronous start-up, synchronizing, and synchronous operation. The model consists of a set of differential equations involving semiconductor switching with constant topology and variable parameters and utilizes phase variables. But an interconversion between phase variables and space phasors is required to take into account the magnetic saturation. The model is then used for a sample system to enable a comparison between experimental and computed results. This comparison is used to assess the accuracy, validity, and usefulness of the model. Furthermore, steady-state behavior of the scheme is explained by means of a simple analysis and illustrated by test results.
Keywords: synchronous induction motor; model; series excited